ANALISIS FAKTOR YANG MEMPENGARUHI PELANGGARAN MERK DAGANG INDONESIA - Kusumastuti, Dora - (Widya Wacana: Jurnal Ilmiah, 2011)
Abstract:Since Indonesia ratified the Agreement Establishing the World Trade Organization(WTO) and its attachements: Annex 1A, B, C: 2, 3, and 4, Indonesia is also tied up to legalizeAgreement Establishing the World Trade Organizationof theUruguay round to the nationallegislation concerning to HaKI (Property Right). As one of developing countries, Indonesia isproperly called as HaKI (Property Right) consumer and the developed countries are as theproducers of HaKI (Property Right). Similar to the other developing countries having loweconomic growth and law enforcement, Indonesia also has problems with disobedience of HaKI(Property Right).Key words:Disobedience of trade mark, law enforcement, HAKI (Property Right)